2018
DOI: 10.5194/acp-18-15879-2018
|View full text |Cite
|
Sign up to set email alerts
|

An automatic observation-based aerosol typing method for EARLINET

Abstract: We present an automatic aerosol classification method based solely on the European Aerosol Research Lidar Network (EARLINET) intensive optical parameters with the aim of building a network-wide classification tool that could provide near-real-time aerosol typing information. The presented method depends on a supervised learning technique and makes use of the Mahalanobis distance function that relates each unclassified measurement to a predefined aerosol type. As a first step (training phase), a reference datas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
63
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 100 publications
(112 reference statements)
0
63
0
Order By: Relevance
“…Amiridis et al (2005) reported a 4-year mean AOD ABL of 0.44±0.16 at 355 nm and a mean LR ABL of 49±25 at 355 nm in summer at Thessaloniki, Greece. According to Papayannis et al (2008), this much higher value of AOD ABL (355) can be attributed to a significantly stronger impact from the Figure 2. Frequency distribution of the aerosol optical depth (AOD), the lidar ratio (LR), the linear particle depolarization ratio (δ), and the Ångström exponent (ÅE) at 355 and 532 nm derived within the atmospheric boundary layer at the EARLINET/ACTRIS lidar site, Warsaw, for the July-September period of 2013, 2015, and 2016.…”
Section: Methodsology Of Lidar Product Retrievalmentioning
confidence: 95%
“…Amiridis et al (2005) reported a 4-year mean AOD ABL of 0.44±0.16 at 355 nm and a mean LR ABL of 49±25 at 355 nm in summer at Thessaloniki, Greece. According to Papayannis et al (2008), this much higher value of AOD ABL (355) can be attributed to a significantly stronger impact from the Figure 2. Frequency distribution of the aerosol optical depth (AOD), the lidar ratio (LR), the linear particle depolarization ratio (δ), and the Ångström exponent (ÅE) at 355 and 532 nm derived within the atmospheric boundary layer at the EARLINET/ACTRIS lidar site, Warsaw, for the July-September period of 2013, 2015, and 2016.…”
Section: Methodsology Of Lidar Product Retrievalmentioning
confidence: 95%
“…In this study, we focus on the main findings regarding those particle optical properties that are used in aerosol-typing efforts with lidar networks and spaceborne lidars. Observations of particle extinction-to-backscatter ratios (lidar ratios), linear depolarization ratios at 355 and 532 nm wavelength, and backscatter-related and extinction-related Ångström exponents (describing the wavelength dependence of backscatter and extinction coefficients from 355 to 1064 nm), as presented here for Central Asian aerosol mixtures, are basic optical parameters in these aerosol-typing efforts and allow us to draw conclusions on the chemical composition (aerosol type), absorption and scattering properties, and size and shape characteristics of the particles (see, e.g., Müller et al, 2007;Burton et al, 2012Burton et al, , 2015Groß et al, 2013;Nicolae et al, 2018;Papagiannopoulos et al, 2016Papagiannopoulos et al, , 2018Voudouri et al, 2019). This article contributes to the steadily growing lidar aerosol-typing data base.…”
mentioning
confidence: 99%
“…These variables are shown to vary with the aerosol type and location and, consequently, EARLINET stations are able to characterize the aerosol load (Müller et al, 2007). Accordingly, EARLINET has established tools for the automatic aerosol characterization (Nicolae et al, 2018;Papagiannopoulos et al, 2018).…”
Section: Earlinetmentioning
confidence: 99%
“…The input lidar ratio value used in the retrieval could significantly affect the results. Papagiannopoulos et al (2018) used 48 ± 13 sr for fresh volcanic particles and 55 ± 7 sr for desert dust particles observed over EARLINET sites in their aerosol classification, which illustrates the variability of this intensive parameter. The uncertainty induced due to the assumption of lidar ratio can easily exceed 20 % (Sasano et al, 1985) and presents an important source that affects the retrieval.…”
Section: Retrieval Of the Particle Parameters In Temporally High Resomentioning
confidence: 99%